Manipulation of Ni Interstitials for Realizing Large Power Factor in TiNiSn‐Based Materials. (6th May 2019) - Ren, Wuyang; Zhu, Hangtian; Mao, Jun; You, Li; Song, Shaowei; Tong, Tian; Bao, Jiming; Luo, Jun; Wang, Zhiming; Ren, Zhifeng
Abstract: Defect engineering has been identified as an effective strategy for improving thermoelectric performance by tailoring electron and phonon transport. TiNiSn is unique due to its naturally formed Ni interstitials, where the interstitial atoms enable strong phonon scattering that results in reduced lattice thermal conductivity, although an adverse effect on mobility is inevitable. Rather than pursuing the conventional strategy of strengthening the interstitial scattering to improve the performance of TiNiSn‐based materials, an attempt is made to minimize the atomic disorder in order to enhance the mobility, which in turn favors a higher power factor. The altered bandgap, and electrical and thermal properties demonstrate that the interstitials can be effectively controlled by intentionally reducing the amount of Ni. Benefiting from the manipulation of the interstitials, significantly enhanced mobility is achieved in the Ni‐deficient composition, resulting in peak power factor of ≈50 µW cm −1 K −2, which is comparable to the best n‐type half‐Heusler compounds. Additionally, the well‐designed composition employing Ni interstitial manipulation and heavy‐element doping exhibits peak ZT of ≈0.73, higher than that of all other reported TiNiSn‐based materials. The unique role of interstitials in either electron or phonon transport is emphasized, and further encouragement for engineering thermoelectric properties by manipulating intrinsic disorder, especially in materials with complex structures, is provided. Abstract : Benefiting from successful manipulation of the intrinsic disorder, remarkably enhanced carrier mobility and power factor are realized in TiNiSn‐based compounds in which the peak power factor is comparable with the best reported n‐type half‐Heusler materials. These positive results point to a new route for the optimization of thermoelectric performance by considering the intrinsic disorder as an extra degree of freedom.